2020
DOI: 10.1117/1.jbo.25.6.066002
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative fluorescence perfusion assessment should be corrected by a measured subject-specific arterial input function

Abstract: Significance: The effects of varying the indocyanine green injection dose, injection rate, physiologic dispersion of dye, and intravenous tubing volume propagate into the shape and magnitude of the arterial input function (AIF) during intraoperative fluorescence perfusion assessment, thereby altering the observed kinetics of the fluorescence images in vivo. Aim: Numerical simulations are used to demonstrate the effect of AIF on metrics derived from tissue concentration curves such as peak fluorescence, time-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…It is suggested that correcting for arterial input function by pulse dye densitometry could improve the currently used quantification methods by reducing the intra-and inter-subject variability. 19 Furthermore, fluorescence imaging can be combined with other methods such as endogenous functional imaging of oxygenation or blood perfusion to increase the capabilities of optical imaging to guide surgery reliably and in real time. 20,21 This report demonstrates the difficulties of visual assessment of fluorescence perfusion imaging in patients with potentially compromised bowel segment following partial mesenteric excision.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that correcting for arterial input function by pulse dye densitometry could improve the currently used quantification methods by reducing the intra-and inter-subject variability. 19 Furthermore, fluorescence imaging can be combined with other methods such as endogenous functional imaging of oxygenation or blood perfusion to increase the capabilities of optical imaging to guide surgery reliably and in real time. 20,21 This report demonstrates the difficulties of visual assessment of fluorescence perfusion imaging in patients with potentially compromised bowel segment following partial mesenteric excision.…”
Section: Discussionmentioning
confidence: 99%
“…What is needed is an intraoperative system that can assess vascular perfusion of bone in the surgical field in real-time, which could guide surgeons in the right amount of bone and soft tissue to debride. Although there are challenges in association with the three-dimensional (3-D) nature of traumatic wounds and open fractures, optical imaging techniques 44 , 45 are uniquely suited to collect data on the inflow/outflow kinetics of complex tissues.…”
Section: Potential Optical Imaging and Sensing Needsmentioning
confidence: 99%
“…However, optical imaging systems are uniquely suited to assess perfusion of bone and deep soft tissues in operating room settings in real-time. 27 , 44 , 45 , 49 …”
Section: Potential Optical Imaging and Sensing Needsmentioning
confidence: 99%
See 2 more Smart Citations